Recycling of Cast Iron Chips by Powder Metallurgy - D.N. Adnyana (Institute for Research and Community Services (LPPM) ITB, 1979)
Abstract. The utilization of cast iron chips as an alternative cheaper raw material in the powder metallurgy industry is currently undergoing development to produce useful products. The present work is concerned with the technology and economy of such as alternative powder processing technique. The mechanical properties of grey cast iron are primarily determined by the proportion of included graphite in the metallic matrix in which the graphite also affects the properties of powdered cast iron chips. The influences of the processing technique on the powder characteristics such as the shape, the size, the loose graphite as well as the subsequent route of compacting and sintering are described. In sintering, the effects of the protective atmosphere used on the properties of sintered compact are discussed. Sari. Penggunaan geram (sisa-sisa pengerjaan) dari besi tuang sebagai bahan baku murah di dalam industry puder metallurgi (logam dalam bentuk serbuk (puder)), kini sedang berkembang untuk membuat produk-produk yang bermanfaat. Di dalam studi ini yang diperhatikan adalah segi-segi teknik dan ekonomi dari proses-proses pembuatan puder. Sifat-sifat mekanis besi tuang kelabu pada dasarnya ditentukan oleh jumlah kandungan grafit di dalam matrik, yang mana kandungan grafit dari besi tuang ini juga mempengaruhi kepada sifat-sifat pudernya. Tulisan ini menguraikan pula tentang pengaruh dari teknik pembuatan puder terhadap : sifat-sifat puder seperti bentuk, besar dan grafit yang terlepas dari matrik dan demikian pula terhadap proses-proses pengepresan dan penyinteran. Didiskusikan pula mengenai pengaruh dari gas yang digunakan untuk proses penyinteran terhadap sifat-sifat produk yang telah disinter.